Refugiados en la globalización aproximaciones filosóficas a los procesos de subjetivación y exclusión socio-política - Pamela Verónica Morales (Les Cahiers ALHIM)
The following work addresses the problems of refugees and asylum seekers in Latin America and the processes of socio-political exclusion in both the country of origin and the country of refuge. Our starting point, any forced migration implies an element of violence to the displaced. This time we will focus particularly on Colombian refugees and asylum seekers in Argentina. From the analysis of the case we approach a reflection on violence and the logic of inclusion and exclusion which is part of modern politics. To do this, we will consider the contributions of Giorgio Agamben on sovereign power and the principals Arendt’s concepts on politics and violence.